A preparation method of a new crystal form of ergothioneine
By performing multiple crystallization treatments of alcohol solvents in the crude ergothionine solution, the problem of insufficient hygrosity resistance and light stability of ergothionine crystals was solved, and a new ergothionine crystal form with high purity and excellent properties was prepared.
Patent Information
- Application Number
- CN202411166969.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-08-23
AI Technical Summary
The prior art cannot effectively improve the hygroscopic resistance and light stability of ergothione crystals.
The first crystallization is performed by adding an alcohol solvent to the crude ergothionine solution, and then adding an alcohol solvent to the complex solution again, controlling the temperature and stirring speed, and performing secondary crystallization. Finally, a new ergothionine crystal form with good hygroscopic resistance and high light stability is obtained through gradient cooling and drying.
The prepared new ergothione crystal form has excellent light stability, good anti-hygroscopic properties, and has a high decomposition temperature, and has improved product purity and yield.
Smart Images

Figure CN118908894B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of compound crystals, and in particular to a method for preparing a new crystal form of ergothioneine. Background Art
[0002] Ergothioneine (mercaptohistidine trimethylol salt, ergothioneine, EGT) is a natural antioxidant that can protect cells in the human body and is an important active substance in the body. It has multiple physiological functions such as scavenging free radicals, detoxification, maintaining DNA biosynthesis, normal cell growth and cellular immunity.
[0003] Ergothioneine exists in two isomeric forms: thiol and thione, as follows:
[0004]
[0005] Under light conditions, ergothioneine may degrade and have the smell of trimethylamine. At the same time, the anti-hygroscopicity of ergothioneine needs to be improved.
[0006] Chinese Patent Publication No. CN118221592A discloses a thioneine crystal and a preparation method thereof, wherein the preparation method provided comprises the following steps: stirring thioneine crude product with a purity of 98.0% to 99.9% in 30°C to 40°C warm water until dissolved, cooling down at 5°C to 10°C, and standing to obtain thioneine crystal. However, it does not pay attention to the hygroscopicity resistance and light stability of the product.
[0007] Currently, there is no prior art that discloses novel ergothioneine crystals that can improve the hygroscopicity resistance and light stability.
[0008] Therefore, it is very necessary to develop a preparation method of a new crystal form of thioneine that can solve the above-mentioned technical problems. Summary of the invention
[0009] The object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a new ergothioneine crystal form with good hygroscopicity resistance and higher light stability.
[0010] The present invention is achieved through the following technical solutions:
[0011] A method for preparing a new crystal form of ergothioneine comprises the following steps:
[0012] (1) in thioneine crude product solution, add alcoholic solvent and carry out primary crystallization, obtain primary crystallization sample;
[0013] (2) redissolving the primary crystallized sample in an aqueous solvent to obtain a solution A with a concentration of 250-500 g / L;
[0014] (3) Add an alcohol solvent to solution A until crystals precipitate, preserve the crystals, continue to add the alcohol solvent, grow the crystals, then cool the solution, filter and collect the crystals, and dry them to obtain the product.
[0015] In some embodiments of the present invention, the crude thioneine solution in step (1) is prepared by dissolving crude thioneine in water, or by extracting a solution containing thioneine obtained from a microorganism, followed by crude extraction, chromatography and concentration.
[0016] In some embodiments of the present invention, the concentration of the crude ergothioneine solution in step (1) is 70-150 g / L.
[0017] In some embodiments of the present invention, the alcohol solvent in step (1) includes at least one of anhydrous ethanol and methanol.
[0018] In some embodiments of the present invention, the temperature of the primary crystallization in step (1) is 20-50°C.
[0019] In some embodiments of the present invention, the time of the primary crystallization in step (1) is 0.5-1.5 h.
[0020] In some embodiments of the present invention, the primary crystallization in step (1) is performed while stirring at a rotation speed of 300-800 rpm.
[0021] The size of the crystal particles and the purity of the crystals can be controlled by controlling the stirring speed and the crystal preservation time.
[0022] In some embodiments of the present invention, the amount of the alcohol solvent added in step (1) is 3-7 times the volume of the crude ergothioneine solution. The yield of adding the alcohol solvent to the primary crystallization sample in step (1) is preferably between 85-95%.
[0023] In some embodiments of the present invention, the aqueous solvent in step (2) comprises water or the crude ergothioneine solution in step (1).
[0024] In some embodiments of the present invention, the temperature of solution A in step (2) is controlled at 40-80°C.
[0025] In some embodiments of the present invention, the total consumption of the alcoholic solvent added twice in step (3) is 3.5-6.5 times of the volume of solution A, thereby controlling the purity of thioneine. Too high an addition amount can cause the precipitation of impurities and thus purity to decrease, while too little an addition amount can cause the reduction of overall yield.
[0026] In some embodiments of the present invention, the alcohol solvent in step (3) includes at least one of anhydrous ethanol and methanol.
[0027] In some embodiments of the present invention, after adding the alcohol solvent in step (3), the temperature is controlled to be 40-80°C.
[0028] In some embodiments of the present invention, the crystal preservation time in step (3) is 0.5-2.5 hours, which promotes the stable growth of grains.
[0029] In some embodiments of the present invention, before the crystals are precipitated in step (3), stirring is performed at a speed of 200-500 rpm while adding the alcohol solvent.
[0030] In some embodiments of the present invention, the crystal growing time in step (3) is 0.5-3h.
[0031] In some embodiments of the present invention, step (3) is performed by gradient cooling.
[0032] In some embodiments of the present invention, the gradient cooling rate is 10°C per hour, and the temperature is lowered to 25-50°C.
[0033] In some embodiments of the present invention, the drying temperature in step (3) is 50-80°C.
[0034] In some preferred embodiments of the present invention, the preparation method comprises the following steps:
[0035] (1) the crude thioneine product is dissolved in water to prepare a crude thioneine solution of 70-150g / L, methanol or anhydrous ethanol is added, the temperature is controlled at 20-50°C, and stirred at a rotating speed of 300-800rpm, and a primary crystallization is performed, and the crystal is preserved for 0.5-1.5h to obtain a primary crystallization sample;
[0036] (2) the primary crystallization sample is redissolved in water or the crude thioneine solution of step (1), and a solution A having a concentration of 250-500 g / L is obtained, and the temperature is controlled at 40-80 ° C;
[0037] (3) Add methanol or anhydrous ethanol to solution A, keep the temperature constant, and stir at 200-500 rpm until crystals precipitate. Keep the crystals for 0.5-2.5 h, continue to add methanol or anhydrous ethanol, and the total amount of methanol or anhydrous ethanol added twice is 3.5-6.5 times the volume of solution A. Keep the temperature constant and grow the crystals for 0.5-3 h, then gradually reduce the temperature by 10° C. every hour until the temperature reaches 25-50° C., collect the crystals by filtration, and dry them in an oven at 50-80° C. to obtain the product.
[0038] The beneficial effects of the present invention are:
[0039] The present invention optimizes the concentration of the solution in the secondary crystallization process, and the finally prepared new ergothioneine crystal has excellent light stability, good anti-hygroscopicity and high decomposition temperature resistance.
[0040] The present invention optimizes the amount of alcohol solvent used in the secondary crystallization process, thereby ensuring good light stability and anti-hygroscopicity performance while also improving the purity and yield of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is the scanning electron microscope image of the new crystal form of thioneine of embodiment 1.
[0042] Figure 2 It is the scanning electron microscope image of embodiment 3 thioneine new crystal form.
[0043] Figure 3 It is the scanning electron microscope image of embodiment 4 thioneine new crystal form.
[0044] Figure 4 It is the scanning electron microscope image of the new crystal form of thioneine of comparative example 5.
[0045] Figure 5 This is a scanning electron micrograph of a commercially available ergothioneine product.
[0046] Figure 6 It is the powder X-ray diffraction pattern of the new crystal form of thioneine of embodiment 1.
[0047] Figure 7 It is the powder X-ray diffraction pattern of embodiment 3 thioneine new crystal form.
[0048] Figure 8 It is the powder X-ray diffraction pattern of embodiment 4 thioneine new crystal form.
[0049] Fig. 9 The figure is the powder X-ray diffraction pattern of the new crystal form of thioneine of comparative example 5.
[0050] Fig.10 It is the powder X-ray diffraction pattern of commercially available ergothioneine products.
[0051] Fig.11 It is the thermogravimetric analysis diagram of the new crystal form of thioneine of Example 3.
[0052] Fig.12 It is the thermogravimetric analysis diagram of commercially available ergothioneine products. DETAILED DESCRIPTION
[0053] The present invention will be further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. However, these embodiments are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.
[0054] Example 1
[0055] A preparation method of a new crystal form of ergothioneine, the steps are as follows:
[0056] (1) thioneine crude product is dissolved in water to prepare 70g / L thioneine crude product solution, methanol is added (the addition amount of methanol is 5 times of the volume of thioneine crude product solution), temperature is controlled at 20 DEG C, stirred at 300rpm rotating speed simultaneously, primary crystallization is carried out, crystal preservation is 0.5h, and primary crystallization sample is obtained;
[0057] (2) redissolving the primary crystallized sample in water to obtain a solution A with a concentration of 250 g / L, and controlling the temperature at 40° C.
[0058] (3) methanol is added to solution A, the temperature is kept constant, and stirring is performed at a rotating speed of 200 rpm until crystals are precipitated, and the crystal is preserved for 0.5 h, and methanol is continued to be added, and the total amount of methanol added twice is 3.5 times of the volume of solution A, and the temperature is kept constant, and the crystal is cultivated for 0.5, and then the temperature is gradually lowered, and the temperature is lowered by 10 ° C every 1 h, and the temperature is lowered to 25 ° C, and the crystals are collected by filtration, and after drying in a 50 ° C baking oven, a new crystal form of ergothioneine is obtained, which has Figure 1 The scanning electron micrographs and Figure 6 The powder X-ray diffraction pattern measured using Cu-Kα radiation is shown.
[0059] The purity of the ergothioneine crystals is 99.97%, and the yield is 90%.
[0060] Example 2
[0061] A preparation method of a new crystal form of ergothioneine, the steps are as follows:
[0062] (1) thioneine crude product is dissolved in water to prepare the thioneine crude product solution of 150g / L, anhydrous ethanol (the addition of anhydrous ethanol is 6.5 times of the volume of the thioneine crude product solution), temperature is controlled at 50 DEG C, stirred at 800rpm rotating speed simultaneously, primary crystallization is carried out, crystal preservation 1.5h, and a primary crystallization sample is obtained;
[0063] (2) redissolving the primary crystallized sample in water to obtain a solution A with a concentration of 500 g / L, and controlling the temperature at 80° C.
[0064] (3) Add anhydrous ethanol to solution A, keep the temperature constant, and stir at 500 rpm until crystals precipitate. Keep the crystals for 2.5 hours, continue to add anhydrous ethanol, and the total amount of anhydrous ethanol added twice is 6.5 times the volume of solution A. Keep the temperature constant and grow the crystals for 3 hours. Then, gradually reduce the temperature by 10°C every hour until the temperature reaches 50°C. Filter and collect the crystals, and dry them in an oven at 80°C.
[0065] The purity of the ergothioneine crystals is 99.99%, and the yield is 92%.
[0066] Example 3
[0067] A preparation method of a new crystal form of ergothioneine, the steps are as follows:
[0068] (1) thioneine crude product is dissolved in water to prepare a thioneine crude product solution of 110g / L, methanol is added (the addition amount of methanol is 3.5 times of the volume of the thioneine crude product solution), temperature is controlled at 35 DEG C, stirred at a rotating speed of 600rpm, and primary crystallization is carried out, and crystal preservation is 1h to obtain a primary crystallization sample;
[0069] (2) redissolving the primary crystallized sample in water to obtain a solution A with a concentration of 400 g / L, and controlling the temperature at 60° C.
[0070] (3) methanol was added to solution A, the temperature was kept constant, and the mixture was stirred at 350 rpm until crystals were precipitated. The crystals were kept for 1.5 h, and methanol was added. The total amount of methanol added twice was 5 times of the volume of solution A. The temperature was kept constant. The crystals were grown for 2 h, and then the temperature was gradually lowered by 10 ° C every 1 h. The crystals were cooled to 35 ° C, and the crystals were collected by filtration. After drying in a 70 ° C baking oven, a new crystal of ergothioneine was obtained. Figure 2 The scanning electron micrographs and Figure 7 The powder X-ray diffraction pattern measured using Cu-Kα radiation is shown.
[0071] The purity of the ergothioneine crystals is 99.98%, and the yield is 91.5%.
[0072] Example 4
[0073] A preparation method of a new crystal form of ergothioneine, the steps are as follows:
[0074] (1) thioneine crude product is dissolved in water to prepare a thioneine crude product solution of 120g / L, methanol is added (the addition amount of methanol is 3 times of the volume of the thioneine crude product solution), the temperature is controlled at 30 DEG C, stirred at a rotating speed of 500rpm, and a primary crystallization is carried out, and the crystal is preserved for 1h to obtain a primary crystallization sample;
[0075] (2) the primary crystallization sample is redissolved in the crude thioneine solution of step (1), and a solution A having a concentration of 350 g / L is obtained, and temperature is controlled at 70 ° C;
[0076] (3) methanol was added to solution A, the temperature was kept constant, and the mixture was stirred at 300 rpm until crystals were precipitated. The crystals were kept for 2 h, and methanol was added twice. The total amount of methanol added was 5.5 times of the volume of solution A. The temperature was kept constant. The crystals were grown for 1.5 h, and then the temperature was gradually lowered by 10 ° C every 1 h. The crystals were cooled to 40 ° C, and the crystals were collected by filtration. After drying in a 60 ° C baking oven, a new crystal form of ergothioneine was obtained. Figure 3 The scanning electron micrographs and Figure 8 The powder X-ray diffraction pattern measured using Cu-Kα radiation is shown.
[0077] The purity of the ergothioneine crystals is 99.96%, and the yield is 92.5%.
[0078] Comparative Example 1
[0079] The only difference from Example 3 is that the concentration of solution A in step (2) is different, which is 200 g / L, and the other conditions are the same.
[0080] The purity of the ergothioneine crystals is 99.99%, and the yield is 85%.
[0081] Comparative Example 2
[0082] The only difference from Example 3 is that the concentration of solution A in step (2) is different, which is 600 g / L, and the other conditions are the same.
[0083] The purity of the ergothioneine crystals was 95.96%, and the yield was 91.2%.
[0084] Comparative Example 3
[0085] The difference with Example 3 is only that the total consumption of adding methanol twice in step (3) is 3 times of solution A volume, and all the other conditions are all the same. The purity of thioneine crystal is 98.24%, and yield is 85%.
[0086] Comparative Example 4
[0087] The difference with Example 3 is only that the total consumption of adding methanol twice in step (3) is 7 times of solution A volume, and all the other conditions are all the same. The purity of thioneine crystal is 94.15%, and yield is 91.5%.
[0088] Comparative Example 5
[0089] Compared with Example 3, only one crystallization is performed, that is, the one crystallization sample obtained in step (1) of Example 3 has Figure 4Scanning electron micrograph shown.
[0090] Test Example 1 Moisture absorption test
[0091] The testing method is: select 10 new 20mL glass bottles, fill embodiment 1-4, comparative example 1-5 and commercially available thioneine crystals respectively, clean and place in 105 DEG C of oven drying to constant weight, and do a good job of numbering and recording gram weight; After the embodiment and comparative example samples and commercially available products are dried to constant weight, 1g of powder is filled in a glass bottle respectively, and placed in a constant temperature and humidity chamber (room temperature, 95% humidity); The sample is weighed every 24h until the sample is constant weight; The moisture absorption rate is then calculated, and the results are shown in Table 1. The scanning electron microscope image of commercially available thioneine crystals is as shown in Table 1. Figure 5 , the powder X-ray diffraction pattern is as follows Fig.10 The following test examples are all tested using this commercially available product.
[0092] Table 1
[0093]
[0094] Test Example 2XRD Detection
[0095] Testing equipment and number: D / max2500 / PC rotating target X-ray diffractometer;
[0096] Testing basis: "Chinese Pharmacopoeia" 2015 Part IV 0451 X-ray diffraction method.
[0097] Example 1 Test results are as follows Figure 6 As shown, the test results of Example 3 and Example 4 are as follows Figure 7 , Figure 8 As shown, the test results of Comparative Example 5 are as follows Fig. 9 As shown, the test results of commercially available products are as follows Fig.10 shown.
[0098] Test Example 3 Odor Detection and Light Stability Detection
[0099] Testing method is: first different thioneine samples are dried to constant weight, and the transparent glass bottle (with lid) of 20mL is dried to constant weight, and the content of thioneine is tested synchronously, 3 parallel samples per group;
[0100] Weigh 1g of sample powder into a glass bottle, judge whether the initial sample has taste, and record;
[0101] Transfer to sunlight and evaluate the taste after 1 and 2 weeks of exposure;
[0102] After 4 weeks of illumination, the ergothioneine content in the powder was tested again to check the retention rate of ergothioneine.
[0103] Taste evaluation method: The sample is in a bottle with a cover. After the light exposure is completed, the bottle cover is opened and people put their noses close to smell the odor. Each group requires 5 people to make the evaluation.
[0104] Ergothioneine powder retention rate test method:
[0105] 1) thioneine powder before initial illumination is dried to constant weight, 0.1g powder is weighed, dissolved in 100mL water, the concentration a1 of thioneine is tested, and then the content of thioneine is converted into: content=a1 / 1*100%;
[0106] 2) content after illumination 4 weeks: thioneine powder after illumination 4 weeks is dried to constant weight, 0.1g powder is weighed, dissolved in 100mL water, the concentration a2 of thioneine is tested, and then converted to the content of thioneine: content=a2 / 1*100%;
[0107] 3) Light retention rate after 4 weeks: retention rate (%) = (a1-a2) / a1*100%.
[0108] The test results are shown in Table 2.
[0109] Table 2 Odor detection and light stability test results
[0110]
[0111] Test Example 4 Thermogravimetric Analysis
[0112] Temperature range: room temperature to 800°C; temperature control speed: 10°C / min; atmosphere: nitrogen atmosphere.
[0113] Example 3 Test results are as follows Fig.11 As shown in Figure 2, the maximum weight loss temperature is 304.06°C. The test results of commercially available products are as follows: Fig.12 As shown, the maximum weight loss temperature is 299.93° C. The maximum weight loss temperatures of the crystal samples of various embodiments of the present invention are all higher than those of commercially available products, indicating that the crystal samples of the present invention have good thermal stability.
[0114] Test Example 5 Melting Point Test
[0115] The present invention refers to GB / T 617-2006 4.2 to determine the melting point of thioneine crystals. The melting point / melting range measured in Example 3 is 275-277°C.
[0116] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A method for preparing a new crystal form of thioneine, characterized in that, The steps include: (1) adding an alcohol solvent to a crude ergothioneine solution for primary crystallization to obtain a primary crystal sample; (2) redissolving the primary crystallized sample in an aqueous solvent to obtain a solution A with a concentration of 250-500 g / L; (3) Add an alcohol solvent to solution A until crystals precipitate, preserve the crystals, continue to add the alcohol solvent, grow the crystals, then cool down, filter and collect the crystals, and dry them to obtain the product; The total amount of the alcohol solvent used in step (3) is 3.5-6.5 times the volume of solution A; The alcohol solvent in step (1) or step (3) includes at least one of anhydrous ethanol and methanol.
2. The preparation method according to claim 1, characterized in that: The aqueous solvent in step (2) includes water or the crude ergothioneine solution in step (1).
3. The preparation method according to claim 1 or 2, characterized in that: The crude thioneine solution in step (1) is prepared by dissolving crude thioneine in water, or by extracting a solution containing thioneine from a microorganism, subjecting it to crude extraction, chromatography and concentration.
4. The preparation method according to claim 1, characterized in that: The concentration of the crude ergothioneine solution in step (1) is 70-150 g / L.
5. The preparation method according to claim 1, characterized in that: The temperature of the primary crystallization in step (1) is 20-50° C.; the time of the primary crystallization is 0.5-1.5 h; the primary crystallization is stirred at a speed of 300-800 rpm; and the amount of the alcohol solvent added is 3-7 times the volume of the crude ergothioneine solution.
6. The preparation method according to claim 1, characterized in that: The temperature of solution A in step (2) is controlled at 40-80°C.
7. The preparation method according to claim 1, characterized in that: After adding the alcohol solvent in step (3), the temperature is controlled to be 40-80°C; the crystal preservation time is 0.5-2.5 hours; before crystal precipitation, stirring is performed at a speed of 200-500 rpm while adding the alcohol solvent; the crystal cultivation time is 0.5-3 hours.
8. The preparation method according to claim 1, characterized in that: The cooling in step (3) is performed by gradient cooling.
9. The preparation method according to claim 8, characterized in that: The gradient cooling rate is 10°C per hour, and the temperature is lowered to 25-50°C.
10. The preparation method according to claim 1, characterized in that: The drying temperature in step (3) is 50-80°C.
Citation Information
Patent Citations
Ergothioneine crystal and preparation method thereof
CN118221592A
Method for industrially preparing high-purity ergothioneine
CN113666873A